¿Reconoce esta clave diagnóstica? - Jennifer Arenas Sepúlveda; Laura Andrea Peña Mejia; Luis Alfonso Correa Londoño; Maria Natalia Mejia Barreneche (Revista de la Asociación Colombiana de Dermatología y Cirugía Dermatológica, 2023)
¿Reconoce esta clave diagnóstica?.